Dark ghost [compact disc, unabridged] - Feehan, Christine (Feehan, Christine. Carpathian novel., 2015)
Andre Boroi has spent centuries battling the undead, holding out against the dark with honor. But now, gravely wounded by master vampire Costin Popescu, Andre will be easy to track - his spilled blood marking the killing trail for Popescu and his hungry band of underlings. Andre₂s only chance is to disappear into the gray mist of the Carpathians. In the mountains in search of a precious crystal, geologist Teagan Joanes suddenly finds herself hunted by those she once trusted. Then she comes across the wounded and irresistible warrior. And with every beat of her heart, Teagan surrenders to a passion she can₂t possibly comprehend.